Improving Energy Efficiency and Response Time of an Offshore Winch Drive with Digital Displacement Motors - Thomas Farsakoglou; Henrik C. Pedersen; Morten K. Ebbesen; Torben Ole Andersen (Modeling, Identification and Control, 2023)
Offshore winch drives require high energy efficiency and control precision, making digital displacement motors an attractive solution due to their high efficiency and potential controllability. However, the response time and the realized energy efficiency of these motors are heavily dependent on the chosen displacement control strategy, especially at low-speed operation. This paper considers various displacement control strategies to investigate whether digital displacement motors are a viable solution for offshore winch drive applications. The motor specifications are derived based on the requirements of a commercial offshore winch drive system. The analysis reveals that various displacement control strategies should be used across the drive's operational speed range to ensure both satisfactory performance and high efficiency. Full-stroke and partial-stroke strategies are optimal for speeds above 28 rpm and 20 rpm, respectively, but unsuited for lower-speed operation. For speeds below 20 rpm, an improved sequential-stroke strategy is therefore presented. The proposed displacement control strategy provides instantaneous motor response and maintains high energy efficiency, although its robustness is slightly reduced at higher operating speeds above 20 rpm.